Coaching the coach: Intervention effects on need-supportive coaching behavior and athlete motivation and engagement - Reynders, B.; Vansteenkiste, M.; van Puyenbroeck, S.; Aelterman, N.; De Backer, M.; Delrue, J.; De Muynck, G. J.; Fransen, K.; Haerens, L.; Broek, G. V. (Psychology of Sport and Exercise, 2019)
The present intervention study examined whether youth sport coaches can be trained in adopting a need-supportive (i.e., autonomy support and structure) coaching style to the benefit of youth athletes` autonomous motivation and engagement. Participants were 43 coaches (33 men, 10 women) and 326 youth athletes (221 boys, 105 girls), active in 12 team or individual sports. Sport coaches were randomly assigned to either a control or intervention condition. The training involved a workshop trajectory spanning four sessions on how to incorporate a (more) need-supportive coaching style. As for coaches` self-reported coaching style, results of multilevel modelling revealed positive effects on autonomy support and control at posttest, and additional effect on structure and control from pre-test to follow-up (i.e., 4 months later) compared to coaches in the control condition. As for athletes` reports, multilevel modelling showed that athletes of coaches in the intervention, relative to those involved in the control group, perceived their coach to be more autonomy-supportive, more structuring, and less chaotic from pre-to posttest, with these effects being more pronounced for athletes of team sports. Further, athletes of coaches in the intervention group reported being more autonomously motivated and more engaged compared to those of coaches in the control group. Overall, the present findings indicate that sport coaches can become more skilled in adopting a need-supportive coaching style, to the benefit of athletes` autonomous motivation and engagement.